2020
DOI: 10.3389/fspor.2020.583848
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Walking Speed in the Wild

Abstract: An individual's physical activity substantially impacts the potential for prevention and recovery from diverse health issues, including cardiovascular diseases. Precise quantification of a patient's level of day-to-day physical activity, which can be characterized by the type, intensity, and duration of movement, is crucial for clinicians. Walking is a primary and fundamental physical activity for most individuals. Walking speed has been shown to correlate with various heart pathologies and overall function. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…People take thousands of steps per day, but real-world walking occurs in many separate bouts, most of which are short, with 90% being less than 100 steps in duration 34 . Speed is relatively consistent within each bout, but varies across bouts 27 . This fragmentation presents a challenge for collecting optimization data and efficiently fine-tuning assistance.…”
Section: Mainmentioning
confidence: 99%
See 2 more Smart Citations
“…People take thousands of steps per day, but real-world walking occurs in many separate bouts, most of which are short, with 90% being less than 100 steps in duration 34 . Speed is relatively consistent within each bout, but varies across bouts 27 . This fragmentation presents a challenge for collecting optimization data and efficiently fine-tuning assistance.…”
Section: Mainmentioning
confidence: 99%
“…We developed a speed-adaptive controller to adjust assistance based on natural variations in walking speed. People vary their walking speed widely during the day 27 in response to changes in context 28 and constraints 29 . Variations in speed complicate exoskeleton control and may help explain why assistive devices that reduce walking effort during steady walking on a treadmill have not provided similar benefits during use under more natural conditions 17 .…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Using trigger events, we split continuous IMU data into walking trials in MATLAB. We extracted one stride from each walking trial based on gait events identified using a one-dimensional continuous wavelet transform of the foot vertical acceleration data (Baroudi et al 2020; Hafer et al 2020). Finally, we used a Kalman filter to estimate sensor orientations in a global reference frame from raw linear acceleration, angular velocity, and magnetometer signals (Holmstrom 2016 Oct 26) and exported the IMU orientation data in quaternion format.…”
Section: Methodsmentioning
confidence: 99%
“…These methods have been implemented for single sensors placed on the trunk (85-87), waist (88,89), shank (90), ear (76) and foot (91,92). A thigh-based singlepoint IMU, the Activpal (PAL Technologies, Glasgow, Scotland), has also been used to measure mobility (73,93). However, this sensor has, to our knowledge, not analysed gait metrics beyond step identification in a single-point system.…”
Section: Inertial Sensor-based Gait Analysismentioning
confidence: 99%